Case Report: Not all recurrent “idiopathic” anaphylaxis is idiopathic - Khalil, Sally Mahgoub; Rahim, Sherin; Mobayed, Hassan; Al-Nesf, Maryam Ali; Bahna, Sami (Frontiers in Allergy, 2025)
IntroductionAnaphylaxis is the most severe manifestation of systemic immediate hypersensitivity, yet the underlying trigger often remains elusive. When routine history and allergy testing fail to identify a cause, the condition is classified as idiopathic anaphylaxis. Food additives, although uncommon culprits, may be overlooked, particularly in atopic individuals.MethodsWe report a case of a 39-year-old woman with recurrent anaphylaxis initially diagnosed as idiopathic. Standard allergy testing, including extended skin prick and specific IgE panels, was negative. Due to a temporal association with restaurant-prepared food, an additive hypersensitivity was suspected. A detailed dietary history and targeted skin prick testing were employed using both commercial and in-house preparations of food colorants.ResultsSPT was positive for carmine-containing red food colorants, including a commercially available gel and a prepared cochineal extract. Control subjects tested negative. sIgE to carmine was equivocal. The patient was educated about allergen avoidance and has remained symptom-free following elimination of carmine from her diet, cosmetics, and medications.ConclusionThis case underscores the importance of considering food additives, particularly carmine, in patients with unexplained anaphylaxis. Structured re-evaluation, patient-guided dietary review, and custom allergen testing may be essential in identifying hidden allergens. Clinicians should be vigilant about uncommon triggers when routine investigations fail to identify the cause.